Perancangan Sistem Optimasi Smart Solar Electrical pada Pembangkit Listrik Tenaga Surya (PLTS) dengan Metode Tracking Dual Axis Technology - Rean Khotama; Dian Budhi Santoso; Arnisa Stefanie (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2020)
The Solar Power Plant is an environmentally friendly, and Indonesia is a tropical country that gets an average of 4.8 kWh of solar light per day. However, in general, the type of solar panel installation is carried out regularly (statistically) at a certain angle so that the solar radiation absorbed by the solar panels is not optimal when the sun turns its back on the solar panel. This study aims to design a site that can optimally absorb sunlight rays using the Tracking Dual Axis Technology method based on the ATmega 2560 microcontroller as a system controller and Light Dependent Resistor (LDR) as a sun tracking sensor. So that it can maximize the absorption of solar radiation by solar panels. The Dual Axis Technology Tracking testers get a maximum Photovoltac voltage of 20.99 volts and a minimum of 19.75 volts and a maximum current of 21.04 mA and a minimum of 14.12 mA.